Primary Nasopharyngeal Adenocarcinoma (NAC) in A Remission Stage of Nasopharyngeal Squamous Carcinoma Patient - WAA, Wan Hassan; KA, M Rajet; N, Md Salleh; R, Ibrahim; BD, Susibalan; WI, Leman (International Journal of Human and Health Sciences (IJHHS), 2022)
Nasopharyngeal adenocarcinoma is an extremely rare entity with the incidence about 0.5% of all nasopharyngeal cancer. We report a case of nasopharyngeal adenocarcinoma (NAC) in a patient who is already on remission of nasopharyngeal squamous carcinoma. He had completed radiotherapy for 35 cycles. However, after remission completed for about 2 years with regular follow up, he was diagnosed with another carcinoma. Due its rarity, treatment modality of nasopharyngeal adenocarcinoma is still debatable as no studies has been shown to be the best modalities. Nasopharyngectomy, neck nodes dissection as well as post-operative radiotherapy are the best treatment of choice for this type of carcinoma. International Journal of Human and Health Sciences Vol. 06 No. 01 January’22 Page: 140-142